The Perceived Impact of COVID-19 on Student Well-Being and the Mediating Role of the University Support: Evidence From France, Germany, Russia, and the UK - Plakhotnik, Maria S.; Volkova, Natalia V.; Jiang, Cuiling; Yahiaoui, Dorra; Pheiffer, Gary; McKay, Kerry; Newman, Sonja; Reißig-Thust, Solveig (Frontiers in Psychology, 2021)
The rapid and unplanned change to teaching and learning in the online format brought by COVID-19 has likely impacted many, if not all, aspects of university students’ lives worldwide. To contribute to the investigation of this change, this study focuses on the impact of the pandemic on student well-being, which has been found to be as important to student lifelong success as their academic achievement. Student well-being has been linked to their engagement and performance in curricular, co-curricular, and extracurricular activities, intrinsic motivation, satisfaction, meaning making, and mental health. The purpose of this study was to examine how student perceptions of their degree completion and future job prospects during the pandemic impact their well-being and what role university support plays in this relationship. We used the conservation of resources theory to frame our study and to develop five hypotheses that were later tested via structural equation modeling. Data were collected from 2707 university students in France, Germany, Russia, and UK via an online survey. The results showed that university support provided by instructors and administration plays a mediating role in the relationship between the perceived impact of COVID-19 on degree completion and future job prospects and levels of student well-being. Student well-being is decreased by their concerns for their degree completion but not by their concerns for future job prospects. In turn, concerns for future job prospects affect student well-being over time. These results suggest that in a “new normal”, universities could increase student well-being by making support to student studies a priority, especially for undergraduates. Also, universities should be aware of the students’ changing emotional responses to crisis and ensure visibility and accessibility of student support.